Smart sensors networks communication technologies and intelligent applications - Xhafa, Fatos; Leu, Fang-Yie; Hung, Li-Ling (London Academic Press, 2017)
Smart Sensors Networks: Communication Technologies and Intelligent Applications explores the latest sensor and sensor networks techniques and applications, showing how networked wireless sensors are used to monitor and gather intelligence from our surrounding environment. It provides a systematic look at the unique characteristics of wireless sensor networks through their usage in a broad range of areas, including healthcare for the elderly, energy consumption, industrial automation, intelligent transportation systems, smart homes and cities, and more. The book shows how sensor-networks work and how they are applied to monitor our surrounding environment. It explores the most important aspects of modern sensors technologies, providing insights on the newest technologies and the systems needed to operate them. Readers will find the book to be an entry point for understanding the fundamental differences between the various sensor technologies and their use in for different scenarios.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Intelligent sensors; Telecommunication systems; Signal processing; Electronic books